Search for HRV-parameters that detect a sympathetic shift in heart failure patients on β-blocker treatment - Zhang, Yanru; de Peuter, Olav R.; Kamphuisen, Pieter W.; Karemaker, John M. (Frontiers in Physiology, 2013)
Background: A sympathetic shift in heart rate variability (HRV) from high, beat-to-beat, to lower frequencies may be an early signal of deterioration in a monitored patient. Most chronic heart failure (CHF) patients receive ß-blockers. This tends to obscure HRV observation by increasing the fast variations. We tested which HRV parameters would still detect the change into a sympathetic state. Methods and results: ß-blocker (Carvedilol®) treated CHF patients underwent a protocol of 10 minutes supine rest, followed by 10 minutes active standing. CHF patients (NYHA Class II-IV) n=15, 10m/5f, mean age 58.4 years (47-72); healthy controls n=29, 18m/11f, mean age 62.9 years (49-78). Interbeat intervals (IBI) were extracted from the finger blood pressure wave (Nexfin®). Both linear and nonlinear HRV analyses were applied that (1) might be able to differentiate patients from healthy controls under resting conditions and (2) detect the change into a sympathetic state in the present short recordings. Linear: mean-IBI, SD-IBI, rMSSD (root mean square of successive differences), pIBI-50 (the proportion of intervals that differs by more than 50 ms from the previous), LF, HF and LF/HF ratio. Nonlinear: SampEn (sample entropy), MSE (Multiscale entropy) and derived: MSV (Multiscale variance) and MSD (Multiscale rMSSD). In the supine resting situation patients differed from controls by having higher HF and, consequently, lower LF/HF. In addition their longer range (τ=6-10) MSE was lower as well. The sympathetic shift was, in controls, detected by mean-IBI, rMSSD, pIBI-50 and LF/HF, all going down; in CHF by mean-IBI, rMSSD, pIBI-50 and MSD (τ=6-10) going down. MSD6-10 introduced here works as a band-pass filter favoring frequencies from 0.02-0.1Conclusions: In ß-blocker treated CHF patients, traditional time domain analysis (mean-IBI, rMSSD, pIBI-50) and MSD6-10 provide the most useful information to detect a condition change.